Allelic diversity of the FaOMT gene (mesifurane biosynthesis) in promising strawberry cultivars and selected forms developed at the I.V. Michurin Federal Science Center - A. S. Lyzhin; I. V. Luk’yanchuk (Труды по прикладной ботанике, генетике и селекции)
Background. Fruit aroma is an important consumer trait of strawberry varieties. Identification of genotypes carrying the genes of the aromatic complex in fruits is an important stage in the development of new cultivars with aromatic fruits. The purpose of this study was to analyze the allelic state of the FaOMT fruit aroma gene in strawberry cultivars and selected forms developed at the I.V. Michurin Federal Science Center to identify promising genotypes for use in breeding for fruit aroma.Materials and methods. The research materials were strawberry cultivars and promising selected forms developed at the I.V. Michurin FSC using the methods of introgressive and intervarietal hybridization. Allelic state of the FaOMT gene was identified with the codominant marker FaOMT-SI/NO.Results and conclusion. The FaOMT fruit aroma gene is represented in the studied strawberry varieties and forms by three combinations of alleles: the homozygous state of the functional allele, the heterozygous combination of the alleles, and the homozygous state of the nonfunctional allele. Cvs. ‘Rubinovy kaskad’, ‘Privlekatelnaya’ and ‘Feyerverk’ are characterized by a heterozygous combination of alleles of the FaOMT gene. Cvs. ‘Lastochka’, ‘Pamyati Zubova’, ‘Flora’, ‘Yarkaya’ and ‘Urozhaynaya CGL’ are characterized by the homozygous state of the FaOMT+ allele. Selected strawberry forms 928-12, 26-5, 72-71 and 62-41 have the heterozygous genotype; hybrids 298-19-9-43 and 932-29 are characterized by the homozygous state of the FaOMT+ allele; selected forms 61-12 and 65-26 are characterized by the homozygous state of the nonfunctional FaOMT– allele. Strawberry forms promising for breeding, with the homozygous state of the functional FaOMT+ allele, were identified: cvs. ‘Lastochka’, ‘Pamyati Zubova’, ‘Flora’, ‘Yarkaya’ and ‘Urozhaynaya CGL’, and selected forms 298-19-9-43 and 932-29.